Enhancement of the Anti-Skin Wrinkling Effects of Aloe arborescens Miller Extracts Associated with Lactic Acid Fermentation. (2nd June 2020) - Ro, Hyang Seon; Jang, Hyun Jun; Kim, Gyu Rae; Park, Sang Jin; Lee, Hyeon Yong
Abstract : This work clearly shows that Aloe arborescens but not gels from Aloe vera, a common juice-type product of Aloe, exerted anti-skin wrinkling effects, and these effects were greatly enhanced by lactic acid fermentation with Lactobacillus plantarum . Treatment with the extract from the fermentation process (FE) at a dose of 0.5% highly activated human fibroblast cells by up to 175%, whereas 140% activation and 105% activation were observed with the extract obtained using conventional water extraction (WE) and the gel from A. vera (GE), respectively. The treatment of human fibroblasts with FE at a dose of 0.5% increased collagen production by up to 170% and inhibited MMP-1 synthesis to 48%, which is likely due to its high antioxidant activity because the WE and GE showed markedly lower effects compared with those of the FE. Interestingly, the FE exhibited a profile dominated by relatively low-molecular-weight (MW) polysaccharides: 20% of the total polysaccharides in the FE were in the MW weight range of 600 to 900, whereas 95% of the total polysaccharides in the GE were in the MW range of 200, 000 to 300, 000. This result suggests that the larger polysaccharide molecules in the extract might be broken down during lactic acid fermentation, and the easy penetration of the small molecules in the extract into fibroblast cells thus results in improved anti-skin wrinkling effects. This conclusion is also supported by the finding that the FE and WE, but not the GE, contained similar amounts of barbaloin, a strong antioxidant eluted from A. arborescens through the fermentation process. Therefore, this study strongly indicates that the enhanced anti-skin wrinkling effects of the FE are most likely due to synergistic effects between the barbaloin and the low-MW polysaccharides retained after the fermentation process.